To have a cloth, to have a plan: weaving teaching in the midst of the curricular internship (Revista Apotheke, 2024)
The text essays about and based on teaching paths created in the subject of Curricular Internship in Visual Arts, proposed in the initial training of art educators. The writing unfolds from the appropriation of a raw cotton fabric, a cloth, on which the discipline plan developed. On the cloth, some propositions were executed, but there was also the appropriation of this cloth as an intervention surface, spontaneously by the participants. Thus, the processes of teaching constitution are exercised from poetic and conceptual intercessors, starting from A/R/Tographic (Irwin, 2013) and cartographic (Rolnik, 2016) inspirations, in their methodological intricacies. The theoretical field draws on Larrosa (2004, 2017, 2018), Pereira (2016), Martins (2012), among others. It discusses, in its first part, the establishment of the plan; moves on to writing that narrates operations and exercises in that cloth; and, finally, it addresses aspects of teaching constitution from the perspective of aesthetic training. It points to the fundamental need for aesthetic teaching training, starting, to this end, with theoretical-practical exercises that reflect the possibilities of poetic constitution of teaching.
Keywords: teacher training in visual arts; curricular internship; self constructuon